2006
DOI: 10.1002/jcp.20770
|View full text |Cite
|
Sign up to set email alerts
|

Active caspase‐3 is required for osteoclast differentiation

Abstract: Based on our earlier observation that caspase-3 is present in osteoclasts that are not undergoing apoptosis, we investigated the role of this protein in the differentiation of primary osteoclasts and RAW264.7 cells (Szymczyk KH, et al., 2005, Caspase-3 activity is necessary for RANKL-induced osteoclast differentiation. The Proceedings of the 8th ICCBMT). We noted that osteoclast numbers are decreased in long bones of procaspase-3 knockout mice and that receptor activator of NF-kappaB ligand (RANKL) does not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 51 publications
2
66
0
Order By: Relevance
“…Moreover, caspase-3 is the key caspase responsible for the majority of apoptotic effects [24] . A previous study reported that the activation of caspase-3 was required for osteoclast differentiation [25] . However, the excessive activation of caspases in mature osteoclasts induced the proteolytic cascade of apoptosis [26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, caspase-3 is the key caspase responsible for the majority of apoptotic effects [24] . A previous study reported that the activation of caspase-3 was required for osteoclast differentiation [25] . However, the excessive activation of caspases in mature osteoclasts induced the proteolytic cascade of apoptosis [26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that caspase-3 is required for RANKL-mediated osteoclast differentiation [29]. RANKL induces cleavage of procaspase-3 to caspase-3 and increases caspase-3 activity that, in turn, activates NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…RANKL induces cleavage of procaspase-3 to caspase-3 and increases caspase-3 activity that, in turn, activates NF-κB. Szymczyk et al [29] showed that RAW264.7 procaspase-3 knockdown cells fail to form mature TRACP+ osteoclasts and remain mononuclear. We observed that high D-Glc inhibited caspase-3 activity in response to RANKL in RAW264.7 and BMM cells and this correlated with a predominance of mononuclear cells in cultures and decreased activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-3, the key member of Caspase family, is a frequently activated death protease, catalyzing the specific cleavage of many key cellular proteins (Szymczyk et al, 2006). Therefore, caspase-3 is essential for certain processes associated with the dismantling of the cell and the formation of apoptotic bodies.…”
Section: Caspase-3 Activationmentioning
confidence: 99%